The Role of Adaptive Strategies in the Link Between Sexual Harassment and Burnout in Higher Education: A Three-Path Mediation Model - Abu Elnasr E. Sobaih; Hassane Gharbi; Riadh Brini; Tamer M. Abdelghani (Societies)
Like many other sectors, women in higher education have had negative experiences with sexual harassment. This study examines the coping mechanisms used by female lecturer/researchers and their impact on burnout. Based on Occupational Stress Theory, this research specifically analyzes the mediating role of three coping strategies, i.e., problem-focused coping, emotion-focused coping, and avoidant coping. A quantitative survey was conducted among 800 Tunisian women teacher-researchers, with 613 complete responses that are valid for analysis. The results revealed that under the influence of sexual harassment, women in Tunisian higher education institutions suffer increased burnout. Structural equation analysis shows that emotion-focused coping has a partial mediation effect, while avoidant coping fully mediates the link between harassment and burnout. This research adds to the literature on sexual harassment and suggests implications for the prevention and support of victims in higher education institutions.